PENGARUH CORPORATE GOVERNANCE, STRUKTUR KEPEMILIKAN DAN LEVERAGE TERHADAP MANAJEMEN LABA (Studi pada Perusahaan Go Public Sektor Pertambangan yang terdaftar di Bursa Efek Indonesia tahun 2015-2018) - Natalia Mahdalena; Ardian Prima Putra; Gustita Arnawati Putri (MANAJEMEN DEWANTARA, 2019)
His study discusses to analyze corporate governance, ownership structure and leverage to earning management. The research was conducted at mining companies in Indonesia Stock Exchange 2015-2018. The samples used as many as 29 companies from the population of 83 companies, through a purposive sampling method. The data collection is done by using the method of observation nonparticipant through the financial statemens. The analysis technique aapplied is a technique of multiple linier regression analysis. The results show that audit committee negative effect on earning management, the proportion of commissioners no effect on earning management, managerial ownership no effect on earning management, institutional ownership no effect on earning management and leverage negative effect on earning management.Keyword : audit committee, proportion of commissioners, managerial ownership, institutional ownership, leverage, earning management